Discover your CEO brand : secrets to embracing and maximizing your unique value as a leader - Bates, Suzanne (McGraw Hill-Ascent Audio, 2011)
Ride your personal brand to the highest level in your field! "A combination of inspiration and utility. ... A must-read for leaders, entrepreneurs, or anyone who wants to harness the power of their own personal brand."--DONNY DEUTSCH, television host and Chairman, Deutsch Inc. "Discover Your CEO Brand is an exploration into the art and science, heart and soul, and woof and warp of leadership. The examples are compelling, the reasoning impeccable, and the motivation irresistible." -ALAN WEISS, Ph. D., author of Million Dollar Consulting and The Consulting Bible "I believe strongly that you cannot become a leader in an organization that operates in contrast to your personal values. With the advice provided in Suzanne's book, I am confident readers will find the match that works best for them." -JONATHAN RECKFORD, CEO, Habitat for Humanity International "Whether you are already a famous CEO with a well-established brand or just starting to craft that brand and its impact, this book is an excellent resource and guide. Suzanne Bates motivates all CEOs to develop their personal brand and clearly shows how to do it." -MARSHA FIRESTONE, Ph. D., founder and President, Women Presidents' Organization "Discover Your CEO Brand is a terrific read that sets out a powerful and compelling roadmap for becoming an effective leader. Filled with engaging examples, it is the quintessential guide to building your personal brand." -ANDREW SOBEL, author of All for One and Clients for Life About the Book Steve Jobs did it at Apple. Indra Nooyi did it at Pepsi. Alan Mulally did it at Ford Motor Company. What did these business leaders do exactly? They brought very real, positive change to their organizations by using their unique CEO brand. Now, executive coach Suzanne Bates explains how you can exert the same kind of influence at your company. Discover Your CEO Brand provides the insight, knowledge, and tools you need to discover your own personal CEO style and then develop it into a powerful presence that extends beyond your typical spheres of influence. Bates walks you through the process step by step, teaching you ways to increase your visibility and influence by combining traditional self-branding vehicles like PR and face-to-face networking with new social-media platforms, including Facebook, Twitter, and blogs. No two sets of values, principles, vision, and skills-the foundation of every successful CEO brand-are alike. Whether you're a CEO, team leader, or entrepreneur, you need to discover who you are as a leader, what you believe, and how that defines you. It's not as apparent as you may think. Applying her years of expertise, Bates takes you deep below the surface to find the powerful leadership brand inside you, so you can: Connect with key audiences Elevate your leader profile Attract and retain the best talent Create business opportunities Shape a high-performance culture Drive long-term value within your company It's not about crafting a leadership style out of thin air in order to influence people and "get ahead." It's about discovering your own personal leadership style. It's about connecting with others authentically. It's about instituting change that benefits the company and the people in it. You're about to head down a road to dramatically improving your organization, your career, and your life. Take your first steps with Suzanne Bates and the proven methods she outlines in Discover Your CEO Brand